2018
DOI: 10.1016/j.case.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Rare Case of Recurrent Cardioembolic Stroke Attributed to Multiple Congenital Cardiac Malformations

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, surgical treatment could only be performed on one of four diverticula. 19 Harris et al reported a symptomatic young lady who presented with multiple diverticula and was followed up with heart failure treatment and anticoagulant therapy; the patient's symptoms were seen to improve. 20 We treated our patient with β-blockers, spironolactone, ramipril + hydrochlorothiazide, and warfarin.…”
Section: Discussionmentioning
confidence: 99%
“…However, surgical treatment could only be performed on one of four diverticula. 19 Harris et al reported a symptomatic young lady who presented with multiple diverticula and was followed up with heart failure treatment and anticoagulant therapy; the patient's symptoms were seen to improve. 20 We treated our patient with β-blockers, spironolactone, ramipril + hydrochlorothiazide, and warfarin.…”
Section: Discussionmentioning
confidence: 99%